PERAN KIP KOTA BANDA ACEH DALAM PEMENUHAN AKSESIBILITAS PEMILIH DISABILITAS PADA PEMILU 2024 - Fina Salsabilla; Tasya Anjali; Zikra Ul Khaira; Khansa Najla; Nofriadi Nofriadi (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study aims to analyze the role of the Banda Aceh Independent Election Commission (KIP) in fulfilling accessibility for persons with disabilities in the 2024 General Election and 2024 Regional Head Election. Using a descriptive qualitative approach through in-depth interviews with the Head of KIP Banda Aceh, this study applies Iris Marion Young's (2000) Inclusive Democracy theory with three main indicators: non-discrimination, effective participation, and empowerment. The findings reveal that KIP Banda Aceh has implemented several accessibility programs, including Braille ballots (limited to presidential and DPD RI ballots), priority seating at polling stations, personal assistance, disability community outreach, KPPS officer simulation training, and home-visit voting services for voters unable to attend TPS. Nevertheless, voter turnout among persons with disabilities in the 2024 General Election reached only 47.3% (429 out of 907 registered voters), indicating a gap between physical accessibility provision and substantive participation. This study concludes that KIP Banda Aceh's role remains predominantly at the non-discrimination stage and has not yet fully reached the empowerment stage envisioned by Young's theory, largely due to the absence of systematic evaluation mechanisms and active involvement of the disability community in policy planning.